A Performative Approach to Urban Informality: Learning from Mexico City and Rio de Janeiro - Müller, Frank (Anthropologica, 2019)
In light of perpetuated exclusions in and through urban development, governance and planning along the dichotomy of formality and informality, I argue that informality should be conceived of as a socially embedded and embodied signifier. Building upon recent approaches to overcome the dichotomy, I hence develop a performative approach toward urban informality. I discuss informality as a methodological orientation to rethink power relations inherent to dwelling and confined housing. Engaging in a transnational and mutual learning process, the paper conducts a “disjunctive comparison” (Lazar 2012) between suburban areas of Mexico City and Rio de Janeiro. Building on ethnographic data, I highlight the active integration of wealthier populations in performing informality and demonstrate that, as a socially embedded role and at times strategically appropriated signifier, informality partakes in a deepening precariousness, and in a normalisation of uncertainty as a form of governing in urban Latin America.